Peran Masyarakat Adat Dalam Mempertahankan Eksistensi Hukum Sasi - Benjamin Carel Picauly; Jemmy Jefry Pietersz; Victor Juzuf Sedubun; Vica Jillyan Edsti Saija (Batulis Civil Law Review, 2022)
The purpose of this research is to analyze and find out the function and role of Sasi Law in the management of the environment, natural resources and ecosystems in it by the people in Negeri Seith and Negeri Ouw, Central Maluku district, and regulations in Seith and Ouw countries in maintaining the existence of Sasi law. This research method is empirical law, which is a research based on field data by taking data according to the sample and conducting an assessment of positive legal provisions and legal principles. The results of the study show that the implementation of Sasi is currently experiencing degradation because it has not been carried out as the implementation of Sasi was originally, even though Sasi has been considered as part of customary law in each Negeri. The regulation of Sasi is not regulated in a Negeri Regulation so that it binds the community and people in each Negeri, as well as being a guide for the next generation to be maintained.